Comparative Proteomic Analysis Reveals New Insights Into the Common and Specific Metabolic Regulation of the Diatom Skeletonema dohrnii to the Silicate and Temperature Availability - Thangaraj, Satheeswaran; Giordano, Mario; Sun, Jun (Frontiers in Plant Science, 2020)
Silicate (Si) and temperature are essential drivers for diatom growth and development in the ocean. Response of diatoms to these particular stress has been investigated, however, it is not known their common and specific responses to regulate the intracellular development. Here we investigated the combination of physiological characteristics and comparative proteomics of diatom Skeletonema dohrnii grown in silicate and temperature limited conditions. Results show that cell carbon and lipid quotas were higher at lower temperature cells, whereas cellular phosphate was higher in cells grown with lower Si. In silicate limitation cells, nitrate transporters were down-regulated and resulted in lower nitrate assimilation, whereas, the phosphate transporters and its assimilation were reduced in lower temperature condition. In photosynthesis, lower silicate caused a reduction in the linear electron flow and NADPH production, whereas cycling electron transport and ATP production was limited by lower temperature. Concerning cell cycle, imbalances in the translation process was observed in lower silicate cells, whereas, impact in the transcription mechanism was observed in lower temperature cells. However, proteins associated with carbon fixation and photorespiration were downregulated in both stress conditions, while the carbohydrate and lipid synthesis proteins were upregulated. Our results showed new insights into the common and specific responses on the proteome and physiology of S.dohrnii to silicate and temperature limitation, provided particular nutrients (Si) and temperature depending mechanism in diatoms.